2011
DOI: 10.1124/dmd.111.038646
|View full text |Cite
|
Sign up to set email alerts
|

Complex Drug Interactions of HIV Protease Inhibitors 2: In Vivo Induction and In Vitro to In Vivo Correlation of Induction of Cytochrome P450 1A2, 2B6, and 2C9 by Ritonavir or Nelfinavir

Abstract: ABSTRACT:Drug-drug interactions (DDIs) with the HIV protease inhibitors (PIs) are complex, paradoxical (e.g., ritonavir/alprazolam), and involve multiple mechanisms. As part of a larger study to better understand these DDIs and to devise a framework for in vitro to in vivo prediction of these DDIs, we determined the inductive effect of ϳ2 weeks of administration of two prototypic PIs, nelfinavir (NFV), ritonavir (RTV), and rifampin (RIF; induction positive control) on the cytochrome P450 enzymes CYP1A2, CYP2B6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 37 publications
2
45
1
Order By: Relevance
“…Carbamazepine decreases bupropion area under the curve (AUC) by 87% and increases OH-bupropion to bupropion AUC ratio by 11.5-fold (Ketter et al, 1995), suggesting an 11-fold increase in hydroxybupropion formation clearance, assuming that the clearance of hydroxybupropion is unaffected by carbamazepine. Rifampicin decreases bupropion AUC by 46-67% (Loboz et al, 2006) and increases hydroxybupropion formation clearance by 4-fold (2.3-6.8-fold) (Kirby et al, 2011), an effect slightly less than that predicted from the hepatocyte data.…”
Section: Resultsmentioning
confidence: 82%
“…Carbamazepine decreases bupropion area under the curve (AUC) by 87% and increases OH-bupropion to bupropion AUC ratio by 11.5-fold (Ketter et al, 1995), suggesting an 11-fold increase in hydroxybupropion formation clearance, assuming that the clearance of hydroxybupropion is unaffected by carbamazepine. Rifampicin decreases bupropion AUC by 46-67% (Loboz et al, 2006) and increases hydroxybupropion formation clearance by 4-fold (2.3-6.8-fold) (Kirby et al, 2011), an effect slightly less than that predicted from the hepatocyte data.…”
Section: Resultsmentioning
confidence: 82%
“…1 (see text). AUC area under the plasma concentration-time curve is frequently prescribed, and interactions due to ritonavir (21)(22)(23) and telaprevir, which are strong inhibitors. These predictions showed that the interactions with colchicine result in AUC ratios that are never >3.5, whereas ritonavir and telaprevir were confirmed as strong inhibitors with an IR of 0.99 and 0.97, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Ritonavir, which is not only a CYP3A4 inhibitor, was nevertheless included because its properties have been well characterized. Ritonavir is also an inhibitor of CYP2D6 and P-glycoprotein and an inducer of CYP2C9 and CYP2C19 (21)(22)(23). To estimate and validate the IR of ritonavir, we selected interaction studies for which CYP3A4 inhibition was thought to be the major mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive mathematical models incorporating either induction alone or induction in combination with inhibition mechanisms have been applied by a number of authors (Fahmi et al, 2008b;Shou et al, 2008;Fahmi and Ripp, 2010;Kirby et al, 2011;Templeton et al 2011). Dynamic models based on an inducer concentration-time profile to account for the change in enzyme expression have also been proposed (Almond et al, 2009;Fahmi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%